Comparison Analysis of Temperature Treatment on Cutleaf Groundcherrys Leaf and Stem - Lilis Supratman; Raden Teti Rostikawati (Journal Of Biology Education Research (JBER), 2021)
The mouth has a normal microflorane of bacteria as the body's defense. Streptococcus mutans bacteria arebacteria that colonize the surface of teeth which have a role in the formation of dental caries. The leaves ofciplukan (Physalis angulata L.) are rich in polyphenols, alkaloids, and flavonoids which are reported to havequite good antimicrobial activity. The aim of this research was to determine the effect of ethanol extract ofciplukan leaves and stalks mouthwash on Streptococcus mutans bacteria. This rese arch method is purelylaboratory experimental using Streptococcus mutans bacteria culture. The antibacterial power test used theliquid dilution method which was then followed by solid dilution with an incubation period of 28 ° C. Thestatistical analysis test used a descriptive test. The results showed that the ethanol extract of the leaves andstems of ciplukan (Physalis angulata L.) had a minimum inhibitory level (MIC) and a minimum kill rate(MBC) at the same concentration, namely 15%. The temperature of the human oral cavity in cold places tendsto change because the mouth is very close to the outside environment, so this mouthwash can berecommended to minimize bacterial growth in cold areas..